2016
DOI: 10.1093/jxb/erw235
|View full text |Cite
|
Sign up to set email alerts
|

Plant acoustics: in the search of a sound mechanism for sound signaling in plants

Abstract: Being sessile, plants continuously deal with their dynamic and complex surroundings, identifying important cues and reacting with appropriate responses. Consequently, the sensitivity of plants has evolved to perceive a myriad of external stimuli, which ultimately ensures their successful survival. Research over past centuries has established that plants respond to environmental factors such as light, temperature, moisture, and mechanical perturbations (e.g. wind, rain, touch, etc.) by suitably modulating their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 79 publications
8
77
0
2
Order By: Relevance
“…Several possible effects have been proposed to sounds in plants and more specifically in seeds [15, 16]. One of the possible effects is to affect the physical integrity of the pericarp which could facilitate the entry of water and oxygen, increasing germination.…”
Section: Resultsmentioning
confidence: 99%
“…Several possible effects have been proposed to sounds in plants and more specifically in seeds [15, 16]. One of the possible effects is to affect the physical integrity of the pericarp which could facilitate the entry of water and oxygen, increasing germination.…”
Section: Resultsmentioning
confidence: 99%
“…The roles of membrane-bound mechanosensors ( i.e ., mechanosensitive ion channels and wall-associated kinase) in plant mechanosensation have been hypothesized previously (Monshausen and Haswell, 2013). These mechanosensors may play important roles in SV perception as well (Mishra et al, 2016). Previously it was observed that SV treatment alters the expression of mechanosensitive ion channels in Arabidopsis (Ghosh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Being a mechanical pressure wave, SV can induce various physiological changes in plants. In earlier studies, a number of SV-induced cellular responses were noticed, which includes calcium spiking, reactive oxygen species (ROS) generation, enhanced antioxidant enzyme activities, changed physical state of membrane lipids and proteins, increased transcription, translation, and effects on cell cycle (Mishra et al, 2016). Moreover, a recent finding establishes the priming potential of SV; pre-exposure to caterpillar-chewing vibration can induce a chemical defense response in Arabidopsis by virtue of accumulating glucosinolates and anthocyanin (Appel and Cocroft, 2014).…”
mentioning
confidence: 99%
“…This system was assembled using an incubator clamp on a 1585 orbital shaking incubator (VWR, PA, USA). [2] beaker, [3] plastic supporter, [4] speaker, [5] sound generator, [6] flexible tubing, [7] sample receiver, [8] flask swab, [9] lid with two outlets, [10] syringe, [11] 0.45 mm filter, [12] tweezers, [13] cotton. bottle cap [9]; on the second outlet, a syringe [10] with a 0.45 mm filter [11] was attached to generate a pressure difference so that the sample could move from the flask to the beaker.…”
Section: Sound Induction Devicementioning
confidence: 99%
“…This knowledge may eventually lead to the development of technology in fields such as applied microbiology, bioengineering, agroindustry and medicine. Although there have been scientific reports describing the effects of sound on living organisms, especially plants, [1][2][3][4] there are few studies addressing how sound affects unicellular organisms.…”
Section: Introductionmentioning
confidence: 99%